2018
DOI: 10.1111/ens.12321
|View full text |Cite
|
Sign up to set email alerts
|

Sexual identity and sexual attractiveness of a gynandromorph of the lawn ground cricket, Polionemobius mikado (Orthoptera: Trigonidiidae)

Abstract: A gynandromorph adult of the lawn ground cricket Polionemobius mikado (Shiraki, 1913) (Orthoptera: Trigonidiidae) was collected from a natural population. It had complete male forewings and a female ovipositor at the end of abdomen. A normal male that encountered the gynandromorph performed a courtship song and tried to transmit a spermatophore, whereas a normal female was indifferent to the gynandromorph. The gynandromorph showed aggressive behavior toward the normal male but not against the normal female. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…During studies on the biology of crickets (Taniyama et al . 2018; Matsuda et al . 2018), I found that P. mikado has protogynous tendencies and protogyny is regulated by photoperiod.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During studies on the biology of crickets (Taniyama et al . 2018; Matsuda et al . 2018), I found that P. mikado has protogynous tendencies and protogyny is regulated by photoperiod.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, I would like to suggest that the lawn ground cricket, Polionemobius mikado (Shiraki, 1913), a univoltine species with egg-overwintering and adults usually appear in late summer and autumn, would be a suitable animal model to study the adaptive significance of protogyny. During studies on the biology of crickets (Taniyama et al 2018;Matsuda et al 2018), I found that P. mikado has protogynous tendencies and protogyny is regulated by photoperiod. Hence, protogyny in this species is expected to occur seasonally, and therefore, the adaptive significance of protogyny should be considered from the perspective of environmental seasonality of the adult crickets encounter.…”
Section: Introductionmentioning
confidence: 99%